Detection of immunogenic parasite and host-specific proteins in the sera of active and chronic individuals infected with Toxoplasma gondii - Yeng, Chen; Osman, Emelia; Mohamed, Zeehaida; Noordin, Rahmah (Electrophoresis, 2010)
Toxoplasma gondii infection in pregnant women may result in abortion and foetal abnormalities, and may be life‐threatening in immunocompromised hosts. To identify the potential infection markers of this disease, 2‐DE and Western blot methods were employed to study the parasite circulating antigens and host‐specific proteins in the sera of T. gondii‐infected individuals. The comparisons were made between serum protein profiles of infected (n=31) and normal (n=10) subjects. Antigenic proteins were identified by immunoblotting using pooled sera and monoclonal anti‐human IgM‐HRP. Selected protein spots were characterised using mass spectrometry. Prominent differences were observed when serum samples of T. gondii‐infected individuals and normal controls were compared. A significant up‐regulation of host‐specific proteins, α2‐HS glycoprotein and α1‐B glycoprotein, was also observed in the silver‐stained gels of both active and chronic infections. However, only α2‐HS glycoprotein and α1‐B glycoprotein in the active infection showed immunoreactivity in Western blots. In addition, three spots of T. gondii proteins were detected, namely (i) hypothetical protein chrXII: 3984434‐3 TGME 49, (ii) dual specificity protein phosphatase, catalytic domain TGME 49 and (iii) NADPH‐cytochrome p450 reductase TGME 49. Thus, 2‐DE approach followed by Western blotting has enabled the identification of five potential infection markers for the diagnosis of toxoplasmosis: three are parasite‐specific proteins and two are host‐specific proteins.